Bridging perceptual gaps: designers vs. non-designers in urban wayfinding signage preferences - Zhou, Jialu; Ujang, Norsidah; Abd Manan, Mohd Shahrudin; Abdul Aziz, Faziawati (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
As urban environments become increasingly complex and the costs and challenges of infrastructure upgrades continue to rise, wayfinding signage has become an effective solution to cope with urban dynamics due to its low cost and high flexibility. Although the functionality of wayfinding signage has been extensively studied, the perceptual differences between designers and non-designers have not been adequately explored. Ignoring these differences may lead to the overlooking of users’ real and diverse needs, resulting in suboptimal signage performance in practical applications and ultimately a reduction in the overall functionality and user experience of urban spaces. This study aims to bridge this perceptual gap. For this study, we conducted a questionnaire survey in China to compare the visual preferences of designers and non-designers regarding text, shape, color coding, and patterns. The results indicate that designers prioritize functionality and clarity to ensure the effective use of signage in complex urban environments, whereas non-designers prefer wayfinding signages that reflect local cultural symbols and characteristics. Our conclusions suggest that the public’s expectations for wayfinding signage extend beyond basic navigational functions, with an emphasis on cultural expression and visual appeal. Understanding these perceptual differences is crucial in developing design strategies that balance functionality, esthetics, and sustainability, thereby facilitating the sustainable integration of signage into urban landscapes.